Listen to This : Miles Davis and "Bitches Brew" - Svorinich, Victor (Book collections on Project MUSE., 2015)
This title tells the story of Miles Davis's watershed 1969 album, Bitches Brew. It traces its incarnations and inspirations for ten-plus years before its release. The album arrived as the jazz scene waned beneath the rise of rock and roll and as Davis (1926-1991) faced large changes in social conditions affecting the African-American consciousness. This new climate served as a catalyst for an experiment that many considered a major departure. Davis's new music projected rock and roll sensibilities, the experimental essence of 1960s' counterculture, yet also harsh dissonances of African-American reality. Many listeners embraced it, while others misunderstood and rejected it.